Moving prevention of functional impairment upstream: is middle age an ideal time for intervention? - Rebecca T. Brown; Kenneth E. Covinsky (BMC, 2020)
Abstract To live independently, individuals must be able to perform basic activities of daily living (ADLs), including bathing, dressing, and transferring out of a bed or chair. When older adults develop difficulty or the need for help performing ADLs, they experience decreased quality of life and an increased risk of acute care utilization, nursing home admission, and death. For these reasons, slowing or preventing the progression to functional problems is a key focus of the care of older adults. While preventive efforts currently focus mainly on older people, difficulty performing basic ADLs ("functional impairment") affects nearly 15% of middle-aged adults, and this prevalence is increasing. People who develop functional impairment in middle age are at increased risk for adverse outcomes similar to those experienced by older adults. Developing ADL impairment in middle age also impacts work force participation and health expenditures, not just in middle age but also older age. Middle-aged adults have a high capacity for recovery from functional impairment, and many risk factors for developing functional impairment in middle and older age have their roots in mid-life. Taken together, these findings suggest that middle age may be an ideal period to intervene to prevent or delay functional impairment. To address the rising prevalence of functional impairment in middle age, we will need to work on several fronts. These include developing improved prognostic tools to identify middle-aged people at highest risk for functional impairment and developing interventions to prevent or delay impairment among middle-aged people. More broadly, we need to recognize functional impairment in middle age as a problem that is as prevalent and central to health outcomes as many chronic medical conditions.